Microenvironment-tailored nanoassemblies for the diagnosis and therapy of neurodegenerative diseases. Issue 23 (24th May 2021) - Low, Liang Ee; Wang, Qiyue; Chen, Ying; Lin, Peihua; Yang, Shengfei; Gong, Linji; Lee, Jiyoung; Siva, Sangeetaprivya P.; Goh, Bey-Hing; Li, Fangyuan; Ling, Daishun
Abstract : This review discussed the design of stimuli-responsive nanoassemblies that can effectively penetrate BBB and interfere with various pathological factors of NME for effective diagnosis and therapy of neurodegenerative disease. Abstract : Neurodegenerative disorder is an illness involving neural dysfunction/death attributed to complex pathological processes, which eventually lead to the mortality of the host. It is generally recognized through features such as mitochondrial dysfunction, protein aggregation, oxidative stress, metal ions dyshomeostasis, membrane potential change, neuroinflammation and neurotransmitter impairment. The aforementioned neuronal dysregulations result in the formation of a complex neurodegenerative microenvironment (NME), and may interact with each other, hindering the performance of therapeutics for neurodegenerative disease (ND). Recently, smart nanoassemblies prepared from functional nanoparticles, which possess the ability to interfere with different NME factors, have shown great promise to enhance the diagnostic and therapeutic efficacy of NDs. Herein, this review highlights the recent advances of stimuli-responsive nanoassemblies that can effectively combat the NME for the management of ND. The first section outlined the NME properties and their interrelations that are exploitable for nanoscale targeting. The discussion is then extended to the controlled assembly of functional nanoparticles for the construction of stimuli-responsive nanoassemblies. Further, the applications of stimuli-responsive nanoassemblies for the enhanced diagnosis and therapy of ND are introduced. Finally, perspectives on the future development of NME-tailored nanomedicines are given.